Left Ventricular Stroke Volume Quantification by Contrast Echocardiography – Comparison of Linear and Flow‐Based Methods to Cardiac Magnetic Resonance. Issue 8 (12th March 2013) - Dele‐Michael, Abiola O.; Fujikura, Kana; Devereux, Richard B.; Islam, Fahmida; Hriljac, Ingrid; Wilson, Sean R.; Lin, Fay; Weinsaft, Jonathan W.
<x xml:space="preserve">Abstract</x> Background Echocardiography (echo)‐quantified LV stroke volume (SV) is widely used to assess systolic performance after acute myocardial infarction (AMI). This study compared 2 common echo approaches – predicated on flow (Doppler) and linear chamber dimensions (Teichholz) – to volumetric SV and global infarct parameters quantified by cardiac magnetic resonance (CMR). Methods Multimodality imaging was performed as part of a post‐AMI registry. For echo, SV was measured by Doppler and Teichholz methods. Cine‐CMR was used for volumetric SV and LVEF quantification, and delayed‐enhancement (DE) CMR for infarct size. Results Overall, 142 patients underwent same day echo and CMR. On echo, mean SV by Teichholz (78 ± 17 mL) was slightly higher than Doppler (75 ± 16 mL; Δ = 3 ± 13 mL; P = 0.02). Compared to SV on CMR (78 ± 18 mL), mean difference by Teichholz (Δ = −0.2 ± 14; P = 0.89) was slightly smaller than Doppler (Δ = −3 ± 14; P = 0.02), but limits of agreement were similar between CMR and echo methods (Teichholz: −28, 27 mL, Doppler: −31, 24 mL). For Teichholz, differences with CMR SV were greatest among patients with anteroseptal or lateral wall hypokinesis (P < 0.05). For Doppler, differences were associated with aortic valve abnormalities or root dilation (P = 0.01). SV by both echo methods decreased stepwise in relation to global LV injury as assessed by CMR‐quantified LVEF and infarct size (P < 0.01). Conclusions Teichholz and Doppler calculated SV yield similar magnitude of agreement with CMR. Teichholz differences with CMR increase with septal or lateral wall contractile dysfunction, whereas Doppler yields increased offsets in patients with aortic remodeling.